2023
DOI: 10.1002/advs.202306056
|View full text |Cite
|
Sign up to set email alerts
|

Respiration‐Triggered Release of Cinnamaldehyde from a Biomolecular Schiff Base Composite for Preservation of Perishable Food

Fei Liu,
Lingyun Kuai,
Chen Lin
et al.

Abstract: One‐third of the food produced worldwide is wasted annually and never consumed, of which ≈ 40–50% are perishable vegetables and fruits (VFs). Although various methods are proposed to reduce this loss, high manufacturing costs and food safety concerns pose significant challenges for the preservation of VFs. Herein, a respiration‐triggered, self‐saving strategy for the preservation of perishable products based on a biomolecular Schiff base composite fabricated by imidization of chitosan and cinnamaldehyde (CS‐Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Upon contact with the moisture generated by the product during storage, the citric acid incorporated in the fibers was solubilized, resulting in the hydrolysis of the imine bond and, subsequently, the release of hexanal, delaying product ripening for 4 days [ 134 ]. In addition, Liu et al [ 135 ] demonstrated the high potential of chitosan modified particles with cinnamaldehyde to extend the shelf life of broccoli and strawberries. The release was triggered by the high transpiration rate of these fruits and vegetables, as shown in Figure 6 c. In this case, no acidic stimulus was incorporated externally, and the authors reported that the release was promoted by the resulting package headspace from the high-rate respiration of the food together with the generated moisture.…”
Section: Reversible Covalent Bonds For Active Food Packagingmentioning
confidence: 99%
“…Upon contact with the moisture generated by the product during storage, the citric acid incorporated in the fibers was solubilized, resulting in the hydrolysis of the imine bond and, subsequently, the release of hexanal, delaying product ripening for 4 days [ 134 ]. In addition, Liu et al [ 135 ] demonstrated the high potential of chitosan modified particles with cinnamaldehyde to extend the shelf life of broccoli and strawberries. The release was triggered by the high transpiration rate of these fruits and vegetables, as shown in Figure 6 c. In this case, no acidic stimulus was incorporated externally, and the authors reported that the release was promoted by the resulting package headspace from the high-rate respiration of the food together with the generated moisture.…”
Section: Reversible Covalent Bonds For Active Food Packagingmentioning
confidence: 99%